Intensity modulated radiation therapy with stereotactic body radiation therapy boost for unfavorable prostate cancer: five-year outcomes - Carrasquilla, Michael; Sholklapper, Tamir; Pepin, Abigail N.; Hodgins, Nicole; Lei, Siyuan; Rashid, Abdul; Danner, Malika; Zwart, Alan; Bolanos, Grecia; Ayoob, Marilyn; Yung, Thomas; Aghdam, Nima; et al. (Frontiers in Oncology, 2023)
Purpose: Intensity-modulated radiation therapy (IMRT) with brachytherapy boost for unfavorable prostate cancer has been shown to improve biochemical relapse-free survival over IMRT alone. 1 A less invasive alternative to brachytherapy is stereotactic body radiation therapy (SBRT). Early outcomes utilizing SBRT boost suggest low rates of high-grade toxicity with maintained patient reported quality of life. Here, we report the 5-year progression free survival (PFS) and prostate cancer specific survival (PCSS) for patients treated with IMRT plus SBRT boost.Materials/Methods: Between 2008 and 2020, 255 patients with unfavorable prostate cancer were treated with robotic SBRT (19.5 Gy in three fractions) followed by fiducial-guided IMRT (45-50.4 Gy) on an institutional protocol. For the first year, patient's PSA was monitored every 3 months, biannually for 2 years, and annually thereafter. Failure was defined using the nadir + 2 ng/mL or a rising PSA with imaging suggestive of recurrence. Detection of recurrence also included digital rectal examination, imaging studies such as MRI, CT, PET/CT, and/or bone scan. PFS and PCSS were calculated using the Kaplan-Meier method.The median follow-up of all patients was 71 months. Per NCCN risk classification, 5% (13/255) of patients had favorable intermediate-risk disease, 23% (57/255) had unfavorable intermediate-risk disease, 40% (102/255) of patients had high-risk disease and 32% (83/255) had very high-risk disease. Androgen deprivation therapy was administered to 80% (204/255) of all patients. Elective pelvic lymph node IMRT was utilized in 28 patients (10%). PFS for all patients at 5 years was 81% (favorable intermediate risk: 91%, unfavorable intermediate risk: 89%, high-risk: 78%, and very-high risk: 72%). PCSS for all patients at 5 years was 97% (favorable intermediate risk: 100%, unfavorable intermediate risk: 100%, high risk: 100%, and very-high risk: 89%).Conclusions: Incidence of failure following IMRT plus SBRT for unfavorable prostate cancer remains low at 5 years.